Advancing Oral Health Equity Through School-Based Oral Health Programs: An Ecological Model and Review - Lynn Gargano; Margaret K. Mason; Mary E. Northridge (Frontiers Media S.A., 2019)
In the United States and elsewhere, children are more likely to have poor oral health if they are homeless, poor, and/or members of racial/ethnic minority and immigrant populations who have suboptimal access to oral health care. As a result, poor oral health serves as the primary marker of social inequality. Here, the authors posit that school-based oral health programs that aim to purposefully address determinants of health care access, health and well-being, and skills-based health education across multiple levels of influence (individual/population, interpersonal, community, and societal/policy) may be more effective in achieving oral health equity than programs that solely target a single outcome (screening, education) or operate only on the individual level. An ecological model is derived from previously published multilevel frameworks and the World Health Organization (WHO) concept of a health-promoting school. The extant literature is then examined for examples of evaluated school-based oral health programs, their locations and outcomes(s)/determinant(s) of interest, the levels of influence they target, and their effectiveness and equity attributes. The authors view school-based oral health programs as vehicles for advancing oral health equity, since vulnerable children often lack access to any preventive or treatment services absent on-site care provision at schools. At the same time, they are incapable of achieving sustainable results without attention to multiple levels of influence. Policy solutions that improve the nutritional quality of children's diets in schools and neighborhoods and engage alternative providers at all levels of influence may be both effective and equitable.